Materials engineering and technologies for production and processing II : selected, peer reviewed papers from the International Conference on Industrial Engineering, May 19-20, 2016, Chelyabinsk, Russian Federation - Radionov, Andrey A.; Mikhailov, G. G.; Vinnik, D. A. (Materials science forum, 2016)
This edition published by results of International Conference on Industrial Engineering (ICIE-2016, May 19-20, 2016, Chelyabinsk, Russian Federation). In the issue are collected scientific papers from area of materials engineering and technologies for materials production and processing in the different areas of modern manufacturing. This collection will be useful for wide range of engineers and scientists from different areas of engineering knowledges. Functional Materials, Structural Materials, Steel, Alloys, Ceramics, Coatings, Hardening, Powder Metallurgy, Hydrometallurgy, Conventional Metallurgical Technologies, Materials Processing, Chemical Engineering Materials Science.